Analitic study of Living Well: a indigenous way of living and the western despair (Research, Society and Development, 2020)
The study emerge as a result of environmental dilemmas of our Society. The questioning starts concerning the indigenous Living Well concept, with argues the future of the planet as a broad discussion between Human beings and the environment. We investigate how the Living Well ideia comes up to Western reality, which paths and directions were taken. The research is essentially qualitative, bibliographic and classify itself as an exploratory study, aiming clarify and criticize concepts. Therefore we  conclude Living Well idea shows up on Western agenda through a couple of movments: The indigenous struggle of self statement and its rights, to resist against a constant coloniality of power and memory;. The other one is called “Western Despair” originated of socio-environmental caos which we are living.